The Galleria mellonella Infection Model for Investigating the Molecular Mechanisms of Legionella Virulence. - Frankel,G; Schroeder,GN (Methods Mol Biol, 2019)
Legionella species evolved virulence factors to exploit protozoa as replicative niches in the environment. Cell culture infection models demonstrated that many of these factors also enable the bacteria to thrive in human macrophages; however, these models do not recapitulate the complex interactions between macrophages, lung epithelial, and additional immune cells, which are crucial to control bacterial infections. Thus, suitable infection models are required to understand which bacterial factors are important to trigger disease. Guinea pigs and, most frequently, mice have been successfully used as mammalian model hosts; however, ethical and economic considerations impede their use in high-throughput screening studies of Legionella isolates or small molecule inhibitors.Here, we describe the larvae of the lepidopteran Galleria mellonella as insect model of Legionella pathogenesis. Larvae can be obtained from commercial suppliers in large numbers, maintained without the need of specialized equipment, and infected by injection. Although lacking the complexity of a mammalian immune system, the larvae mount humoral and cellular immune responses to infection. L. pneumophila strain 130b and other prototype isolates withstand these responses and use the Defective in organelle trafficking/Intracellular multiplication (Dot/Icm) type IV secretion system (T4SS ) to inject effectors enabling survival and replication in hemocytes, insect phagocytes, ultimately leading to the death of the larvae. Differences in virulence between L. pneumophila isolates or gene deletion mutants can be analyzed using indicators of larval health and immune induction, such as pigmentation, mobility, histopathology, and survival. Bacterial replication can be measured by plating hemolymph or by immunofluorescence microscopy of isolated circulating hemocytes from infected larvae. Combined, these straightforward experimental readouts make G. mellonella larvae a versatile model host to rapidly assess the v